The Role of Customer Brand Engagement and Brand Satisfaction in Digital Banking in Lampung - Ria Octavia; Lesmana , Arseta Yudha (FEB - Universitas Lampung, 2022)
People make more transactions at home due to the Covid-19 pandemic, which influences customer behavior in turning financial transactions into digital transactions. The emotional interaction formed through digital services between brands and customers creates opportunities for Customer Brand Engagement. This study aims to examine the influence of Customer Brand Engagement on Online Brand Experience, Online Brand Experience on Brand Loyalty, Brand Experience on Brand Loyalty, and Brand Satisfaction on Brand Loyalty empirically. This study uses the purposive sampling, and the study subjects are active customers of several banks in Indonesia, namely BRI, Mandiri, BCA, and BNI, in the amount of 150 respondents. The research analysis tool used in this study is AMOS with a path analysis method of the Structural Equation Model. This study shows that Customer Brand Engagement has a significant influence on Online Brand Experience, Online Brand Experience has a significant influence on Brand Satisfaction, Online Brand Experience has a significant influence on Brand Loyalty, and Brand Satisfaction has a significant influence on Brand Loyalty. Mobile Banking is one of the biggest expectations of the community in these transactions that results in customers becoming dependent on the bank application brand. This is what creates an Online Brand Experience, and therefore gives an impact on Brand Satisfaction and Brand Loyalty.